Utilization of the Internet of Things in Monitoring Hydroponic Lettuce Cultivation - Nugroh, Heri; Maulindar, Joni; Irawan, Ridwan Dwi (Universitas Bumigora, 2024)
Background: Urban residents who create agricultural systems with hydroponic techniques are very busy and do not have time to monitor plant growth.Objective: This study aims to utilize the Internet of Things (IoT) in monitoring hydroponic lettuce cultivation with the Nutrient Film Technique (NFT) system using ESP32.Methods: The method used in this study is Rule-Based Automatic Control for monitoring hydroponic lettuce cultivation.Result:The results of this research are successfully building a monitoring system with a web interface and mobile interface has been successfully built. The system that was built successfully controlled pH and hydroponic nutrients automatically with a pH sensor accuracy of 97.19% and a nutrient sensor of 97.815%.Conclusion: The implementation of a control and monitoring system for hydroponic lettuce cultivation can be applied because it has high accuracy.